Literasi Kemanfaatan Teknologi terhadap Cyber Terrorism di Era Disrupsi dengan AI (Artificial Intelligence) - Astuti, Sri Ayu (Universitas Muhammadiyah Yogyakarta, 2024)
Without an exception, technology digital improvement with AI (Artificial Intelligence ) function and digital information disclosure have an impact in change of attitude and behavior. Motion and activities in communication and information that related to radicalism and terrorism also take advantage on the improvement of the digital technology which crosses national sovereignty (borderless nation). Terrorism is a form of a Crime against Humanity which categorized as an Extra Ordinary Crime due to its huge psychological impact in exterminating human being. Nowadays terrorism movement enters one extra ordinary stage in organized management, even this organization is internationally well organized. In this digitalized era, radicalism organization and terrorism movement has been invaded to virtual space (cyber). From the recruitment system up to military training and induction is no longer using the old pattern which needs face to face interaction but just through the improvement of digitalized technology (internet). It needs knowledge and recognizes solicitation to act against the criminal act of terrorism through cyber as well as haw the law enforcement related with radicalism and terrorism activities that is conducted through virtual space. In related with that activities, it needs to know the function of electronic verification which is not easy to get and Indonesian may be utilized provision of Undang-Undang Information Transaction Electronic Nomor 1 Tahun 2024 that is revision of the previous law UU Nomor 11 Tahun 2008.